(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the rate and the factors related to medication adherence in elderly patients with acute coronary syndrome Research objects and methods: A cross-sectional and longitudinal study was conducted in all patients 60 years of age or older with acute coronary syndrome discharge from the Cardiovascular Center at Thong Nhat hospital from June 2020 to June 2021. Eligible patients receiving guideline-recommended medications were followed up at least 6 months in Outpatients Department Results: There were 303 patients ≥ 60 years old diagnosed with acute coronary syndrome discharged from the hospital. The prevalence of adherence of 5 classes guideline-recommended drugs was 33.3% at 6 months. Factors related to drug adherence in elderly patients with acute coronary syndrome after multivariate regression analysis included: Older age (> 70 years old), Killip class: II-III-IV and no angioplasty and stent insertion. Conclusion: The rate of medication adherence after acute coronary syndrome in elderly patients is still low. Factors related to medication adherence in elderly patients with acute coronary syndrome are: 1. Older age (> 70 years old), 2. Killip class: II-III-IV, 3. No angioplasty and stent insertion